103k views
3 votes
Answer choices:
0
1
-1
-2 ( chose this and got it wrong so it's not this)

Answer choices: 0 1 -1 -2 ( chose this and got it wrong so it's not this)-example-1
User Syed Waqas
by
6.3k points

2 Answers

3 votes
Average rate of change =(y2 - y1)/(x2 - x1)

For x1=-2, y1 = -1.
For x2=0, y2=-1.

Average rate of change =(-1 + 1)/(0 +1) =0

Answer is 0.
If you connect these 2 points, you will see that line is horizontal, slope is 0, so average rate of change is 0.
User MusikAnimal
by
4.9k points
6 votes
Use the formula for average rate of change over an interval of two points:


(y_2 - y_1)/(x_2 - x_1)

We have two points: (-2, -1) and (0, -1). Plug the values into the formula:


(-1 - (-1))/(0 - (-2)) = (0)/(2) = 0

The average rate of change over the interval [-2,0] is 0.
User Leah Wasser
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.